Efforts to Improve Knowledge and Skills by Adopting Heutagogical Approaches among Technical and Vocational’ Educators - Zakaria, Anies Fazihan; Mohamed, Maziana; Mohamad, Mimi Mohaffyza (Journal of Technical Education and Training, 2021)
Educators play the most crucial role in the education system. They are the cornerstone on which the stability and growth of the education system, including technical and vocational education. In the current situation, the teaching-learning process shall be decided based on the requirements of the learner at every level. With fast-changing technology and education norm, educators faced many challenges and took various way in upgrading and reskilling themselves towards providing practical teaching session. Therefore, heutagogical approaches are appropriate for improving skill and knowledge among them. This study is aimed to determine the efforts level of educator in 13 different Vocational colleges in Johor. A total of 141 educators participated in the survey questionnaire that measures their efforts toward six heutagogical elements in teaching and learning. The finding shows that majority of the educators shows the high level of efforts toward improving their skills and knowledge. The educator’s perception on the implementation of heutagogy in teaching and learning process benefit tremendously in designing practical and sustainable professional development course for educators. Also contributes to heutagogy model in technical and vocational education settings.